2009
DOI: 10.1007/s11426-009-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA restrictive endonucleases by aqueous nanoparticle suspension of methanophosphonate fullerene derivatives and its mechanisms

Abstract: Aqueous nanoparticle suspension of fullerene and its derivatives are currently attracting much attention. To determine the effects of aqueous nanoparticle suspension of a mono-methanophosphonate fullerene and bis-methanophosphonate fullerene (denoted as n-MMPF and n-BMPF, respectively) on the activities of DNA restrictive endonucleases, plasmid pEGFP-N1 was cleaved at a single but differently restrictive site by EcoR I, BamH I, and isozymes Cfr9 I and Xma I, respectively. Both n-MMPF and n-BMPF inhibited the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…172 Study of the effects of aqueous nanoparticles suspension of a mono-methanophosphonate and bis-methanophosphonate fullerene on the activities of DNA restrictive endonucleases showed that aqueous nano-fullerenes might act as inhibitors of DNA restrictive endonucleases. 173 It was demonstrated that fullerene derivatives accelerate the growth of hair in mice and human skin, suggesting that the mechanism that potentiates hair growth in mice is similar to that in humans. 174 A new therapeutic platform showed that fullerene derivatives could inhibit the inflammatory cascade associated with phorbol 12-myristate 13-acetate-induced inflammation.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…172 Study of the effects of aqueous nanoparticles suspension of a mono-methanophosphonate and bis-methanophosphonate fullerene on the activities of DNA restrictive endonucleases showed that aqueous nano-fullerenes might act as inhibitors of DNA restrictive endonucleases. 173 It was demonstrated that fullerene derivatives accelerate the growth of hair in mice and human skin, suggesting that the mechanism that potentiates hair growth in mice is similar to that in humans. 174 A new therapeutic platform showed that fullerene derivatives could inhibit the inflammatory cascade associated with phorbol 12-myristate 13-acetate-induced inflammation.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…14 Gharbi et al reported 15 that fullerenes were powerful antioxidants with no acute or subacute toxicities in mice. Others 16,17 and our group 18 showed that fullerene derivatives could inhibit polymerase chain reaction (PCR) through their interaction with Taq DNA polymerase. Regarding the ecological fate of carbon nanoparticles, we recently mapped 19 the biodistribution of fullerene C 70 in rice plants and reported the generational transfer of C 70 through the plant progeny assisted by natural organic matter (NOM).…”
mentioning
confidence: 99%